Fermentation as pretreatment on the dehydration of Jute (Corchorus olitorius) leaves. - Opiña, Natalie Diane Carbajal (2014.)
A preliminary study was done to establish the drying time of fermented jute. A drying time of 4-5 hours at 55oC to 65oC produced jute leaves that were crisp, with average moisture content of 5.22%. Different fermentation periods were also studied to establish which will be used in the experiment proper. Jute leaves were fermented at different periods with two salt concentration levels. The following combinations were used: 10 days fermentation: 1.5% salt, 10 days fermentation: 3.0% salt, 7 days fermentation: 1.5% salt, and 7 days fermentation: 3.0% salt. The leaves were subjected to dehydration after the complete fermentation schedules. The percent yield was found to be significant higher among samples fermented for 10 days based on ANOVA at 5% level of significance. The rehydration capacity was found to be significantly higher among samples fermented for 7 days. The Gram + cooci and rods were found present in the brines of all formulations, cocci being more dominant. The rehydrated form of jute leaves were subjected to sensory evaluation with 10 well-oriented panelists. The general acceptability of the samples was determined using a 7-point hedonic scale, while intensity of the attributes of the most preferred sample, namely color, aroma, flavor, taste, mouthfeel and acceptability was determined using a 15 cm line scale. The jute leaves fermented for 7 days with 3.0% salt was the most preferred by the panelists. The findings of this study suggest that fermentation prior to dehydration of jute leaves improves the percent yield, rehydration capacity and sensory qualities of the product.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Fermentation; Jute; Corchorus olitorius